Meta-analysis and systematic review of the literature characterizing auditory mismatch negativity in individuals with autism. (April 2018) - Schwartz, Sophie; Shinn-Cunningham, Barbara; Tager-Flusberg, Helen
Highlights: Meta-analyses assessed the auditory MMN response in ASD across 22 publications. Only studies that counterbalanced stimuli showed a trend toward weaker MMN in ASD. Weaker MMN response in ASD was most evident in young children and in nonspeech-based paradigms. MMN response in adolescents and those with below-average verbal IQ is understudied. Targeted study of within-group variability may reveal MMN response anomalies better than between-group analyses. Abstract: A number of past studies have used mismatch negativity (MMN) to identify auditory processing deficits in individuals with autism spectrum disorder (ASD). Our meta-analysis compared MMN responses for individuals with ASD and typically developing controls (TD). We analyzed 67 experiments across 22 publications that employed passive, auditory-based MMN paradigms with ASD and TD participants. Most studies lacked design characteristics that would lead to an accurate description of the MMN. Variability between experiments measuring MMN amplitude was smaller when limited to studies that counterbalanced stimuli. Reduced MMN amplitude was found among young children with ASD compared to controls and in experiments that used nonspeech sounds. Still, few studies included adolescents or those with below-average verbal IQ. Most studies suffered from small sample sizes, and aggregating these data did not reveal significant group differences. This analysis points to a need for research focused specifically on understudied ASD samples using carefully designed MMN experiments. Study of individual differences in MMN may provide further insights into distinct subgroups within the heterogeneous ASD population.